UHPLC–MS/MS Metabolite Fingerprinting and Antimicrobial Mechanisms of Gymnocarpos sclerocephalus (syn. Sclerocephalus arabicus) from the Saharo–Arabian Desert, Libya - Hamed Bogdadi,; Nowar Bhari,; Shamsi Saad Shamsi,; Mukhtar Almukashir,; Ketaam Youness, (AlQalam Journal of Medical and Applied Sciences, 2026)
The Saharo-Arabian desert shrub Gymnocarpos sclerocephalus (Decne) Dahlgren & Thulin (Caryophyllaceae) has medicinal uses, but its phytochemistry and bioactivity are understudied. This research defines the metabolite fingerprint of G. sclerocephalus, isolates key constituents, and assesses its antimicrobial properties and preliminary safety. Using UHPLC–MS/MS, we tentatively identified 35 metabolites, primarily flavonoid glycosides and triterpene saponins. Vitexin, daphnoretin, and quercetin were isolated. The crude extract showed antimicrobial activity (MICs 128–512 µg/mL), with the ethyl acetate fraction being most potent (MIC 32-64 µg/mL). Daphnoretin was effective against S. aureus and B. subtilis (MIC 64 µg/mL). The ethyl acetate fraction inhibited S. aureus biofilm formation by ~80% and disrupted bacterial membrane integrity. Synergy was observed between the ethyl acetate fraction and erythromycin against S. aureus and between daphnoretin and gentamicin against E. coli. The extract showed low cytotoxicity in human fibroblasts (CC50 ~350 µg/mL) and low toxicity in zebrafish embryos. These findings provide a chemotaxonomic profile for G. sclerocephalus and demonstrate its potential as a source of antimicrobial agents.